Historical and legal aspects of documenting land rights - Shulga, M. V. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The level of legal regulation of land ownership and use relations in Ukraine is one of the important factors that reflects the general level of development of the state, the desire for rational and effective use of land plots and the attitude to land resources in general. The implementation of land reform in Ukraine is accompanied by a corresponding reform of the system of registration of rights to land plots, changes to the form of documents certifying rights to land plots. State land registration, initiated by the Land Code of the Ukrainian SSR (1922), laid the foundations for recording information about the legal and economic status of all land users. The Land Code of the Ukrainian SSR (1970), adopted to develop the provisions of the Union Fundamentals of Land Legislation, stipulated that the right to use land of land users (legal entities) is certified by state acts on the right to use land. In contrast, the right to use land of citizens was not documented. It was certified by entries in the land cord books of agricultural enterprises and organizations and the farm books of village councils, and in cities and urban-type settlements - in the register books of the executive committees of local councils. The First Land Code of the Ukrainian SSR (1990), adopted with the gaining of independence by Ukraine, continuing the tradition of legal documents established in Soviet times, provided that the right of ownership or the right to use land was certified by relevant state acts, which were issued by individuals and legal entities and registered by local councils, and the forms of these state acts were established by the Verkhovna Rada of the Ukrainian SSR. The right to temporary use of land was formalized by an agreement, the form of which and the procedure for its registration were established by the Council of Ministers of the Ukrainian SSR. The peculiarity of the Land Code of Ukraine (as amended on March 13, 1992) was that it additionally provided for the State Act on the right of collective ownership of agricultural land, which was issued to agricultural legal entities of private law, among the legal documents. The act was accompanied by a list of members of the agricultural enterprise, in whose collective ownership the land was also located. According to the current Land Code of Ukraine (2001), documents certifying the right of ownership and the right of temporary use were traditionally considered state acts, the forms of which were approved by the Cabinet of Ministers of Ukraine. As a result of the introduction of Art. 126 of the Land Code of Ukraine by the law of 05.03.2009 In addition to the state act, the documents certifying the right of ownership to a land plot additionally included a civil law agreement on the alienation of a land plot and a certificate of the right to inheritance, which was aimed at revitalizing the functioning of land relations and simplifying the documentary registration of land rights. The current version of Art. 126 of the Civil Code of Ukraine “Registration of Real Rights to a Land Plot” provides that the right of ownership and use of a land plot is registered in accordance with the Law of Ukraine “On State Registration of Real Rights to Real Property and Their Encumbrances”. This approach of the legislator to the state registration of real rights to land brings Ukraine closer to European registration systems.